WORK-LIFE BALANCE AND ORGANIZATIONAL SUPPORT ON GENERATION Z EMPLOYEES’ MENTAL HEALTH IN INDONESIA - Hasto Salehhamidzic; Arif Murti Rozamuri (STABILITY : Journal of Management and Business, 2026)
This study examines the effect of work-life balance and organizational support on the mental health of Generation Z employees in Indonesia. A quantitative approach was employed using Structural Equation Modeling with Partial Least Square (SEM-PLS). Data were collected through an online questionnaire using a Likert scale from 115 Generation Z employees in 2024. The analysis was conducted using SmartPLS software. The findings indicate that work-life balance has a positive and significant effect on mental health. In addition, organizational support also positively influences the mental health of Generation Z employees. These results suggest that both individual balance and organizational support play an important role in maintaining employees’ psychological well-being. This study provides practical implications for organizations to design supportive work environments and implement policies that promote mental health among Generation Z employees.